A study of the effectiveness of English for Science and Technology (EST) in promoting content knowledge, language competency and independent study skills among secondary school students in three districts in Perak / Mary Thomas T. O. Thomas, F. Peter G. Francis and Sarjit Singh Utam Singh - T. O. Thomas, Mary Thomas; G. Francis, F. Peter; Utam Singh, Sarjit Singh (2007)
The research was undertaken to establish the effects of English for Science and Technology(EST) in promoting content knowledge, language competency and independent study skills in schools in the Central Perak, Manjung and Kinta Districts. The findings reveal that EST had improved students' proficiency in English Language skills especially in the areas of reading skills and vocabulary enhancement. There was also sufficient evidence to conclude that it had helped learners to cope better with their mainstream subjects especially in the pure sciences. Both teachers and students believed that EST had improved students' content knowledge but the manifestation of students' improvement in content knowledge based on their performance in these subjects is not highly significant. As for the development of independent learning skills, it was discovered that the methodology used in the teaching of this subject did not promote learner autonomy. The findings revealed that the teaching of this subject is still very much teacher dominated. The traditional lecture- style method was the more dominant mode of teaching used in the classroom and whole classroom individual work was more often preferred to small group work or pair work. Some of the problems faced by teachers are:- lack of expertise in integrating content with language teaching which was aggravated by the fact that they had not undergone any relevant training in this area. Besides, the lack of facilities like computer labs limited the manner in which the subject is taught. Finally the lack of confidence to use the spoken language amongst learners had limited student participation in the classroom.